Electrokinetic remediation of fluorine-contaminated soil: Conditioning of anolyte - Kim, Do-Hyung; Jeon, Chil-Sung; Baek, Kitae; Ko, Sung-Hwan; Yang, Jung-Seok (ELSEVIER, 2009)
The feasibility of anolyte conditioning on electrokinetic remediation of fluorine-contaminated soil was investigated with a field soil. The initial concentration Of fluorine, pH and water content in the soil were 414 mg/kg, 8.91 and 15%, respectively. Because the extraction of fluorine generally increased with the soil pH, the pH of the anode compartment was controlled by circulating strong alkaline solution to enhance the extraction Of fluorine during electrokinetic remediation. The removal of fluorine increased with the concentration of the alkaline solution and applied Current density and fluorine removed up to 75.6% within 14 clays. Additionally, anolyte conditioning sharply increased the electro-osmotic flow, which enhanced the removal of fluorine in this study. In many respects, anolyte conditioning in electrokinetic remediation of fluorine-contaminated soil will be a promising technology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: HEAVY-METALS; REMOVAL; COPPER; CU